2009
DOI: 10.1021/np900654a
|View full text |Cite
|
Sign up to set email alerts
|

Diketopiperazines from the Cordyceps-Colonizing Fungus Epicoccum nigrum

Abstract: New diketopiperazines, epicoccins E-H (1-4) and diphenylalazines A (5) and B (6), have been isolated from the solid-substrate fermentation culture of the Cordyceps-colonizing fungus Epicoccum nigrum. The structures of 1-6 were determined primarily by NMR experiments, and the structure of 1 was confirmed by X-ray crystallography. The absolute configurations of 3 and 5 were assigned using the modified Mosher (3) and Marfey's (5) methods, respectively. Compounds 3-5 showed inhibitory effects on HIV-1 replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
64
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(68 citation statements)
references
References 27 publications
1
64
0
3
Order By: Relevance
“…Further correlations from CH 2 (6) to C(4) and C(2) indicated that C(2), C(4), and C (6) were all connected to the same N-atom, N(3), which is consistent with the NMR chemical shifts of these C-atoms. Considering the 13 C-NMR chemical shift of C(2) (d(C) 86.8) and unsaturation requirement for 1, C(2) was connected to the remaining N-atom in 1 by default to complete a 2,2,3,5-tetrasubstituted imidazol-4-one moiety.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Further correlations from CH 2 (6) to C(4) and C(2) indicated that C(2), C(4), and C (6) were all connected to the same N-atom, N(3), which is consistent with the NMR chemical shifts of these C-atoms. Considering the 13 C-NMR chemical shift of C(2) (d(C) 86.8) and unsaturation requirement for 1, C(2) was connected to the remaining N-atom in 1 by default to complete a 2,2,3,5-tetrasubstituted imidazol-4-one moiety.…”
supporting
confidence: 64%
“…), 20-hydroxyaflavinine (5), N-(2-phenylethyl)acetamide (6), and N b -acetyltryptamine (7) by comparison of their NMR and MS data with those reported in [13 -17]. Bacillamide A (3) was initially isolated from the marine bacterium Bacillus sp.…”
mentioning
confidence: 99%
“…Many studies have focused on the ability of this fungus to produce antimicrobial compounds such as epicorazins A–B [12], epicoccins A–D [13], epicoccarines A–B and epipyridone [14], flavipin [15] and epirodins [16]. The production of novel bioactive chemical compounds including siderophores [17], antioxidants [18], inhibitors of HIV-1 replication [19], [20], inhibitors of leucemic cells [21], inhibitors of protease [22], inhibitors of telomerase [23] and fluorescent compounds with biotechnological applications [24], [25] have also been described in Epicoccum isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the 22 fungal species reported to be associated with natural Chinese cordyceps during the 1980s and 1990s (Jiang and Yao 2002), mycoflora investigation indicated the richness of fungal diversity on Chinese cordyceps based on culture-dependent and culture-independent methods (Zhang et al 2010). Many new novel secondary metabolites have been identified from the cordyceps-colonizing fungi (Zhang et al 2007, 2009; Guo et al 2007; Guo, Sun, Gao, Chen, et al 2009; Guo, Sun, Gao, Niu, et al 2009; Ma et al 2011). There is no doubt that the cordyceps-colonizing fungi are important resources for the discovery of novel compounds and for developing medicinal and healthy products.…”
Section: Perspectivementioning
confidence: 99%